2020
DOI: 10.1002/agj2.20095
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization offsets the N2O mitigating effects of cover‐crops and double‐crop soybean in a wheat–sorghum system

Abstract: Cover crops (CCs) have been promoted as a key strategy to reduce nitrous oxide (N 2 O) emissions by scavenging excess mineral nitrogen (N) after cash crop harvest. Optimum N fertilizer application rates are also critical to minimize N 2 O emissions. Integrating these strategies requires research to understand how they interact to drive N 2 O emissions. The objective was to evaluate N 2 O emissions from winter wheat (Triticum aestivum L.) harvest through the subsequent fallow period and grain sorghum [Sorghum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The overall conclusion of the meta-analysis is that cover cropping increases N 2 O emissions only to a very small extent and that the variability is very large. For example, compared to a chemical fallow system, Olofsson and Ernfors [ 39 ] identified the highest value with 1.80 kg N 2 O-N ha -1 for oilseed radish, whereas Preza-Fontes et al [ 40 ] identified the lowest emissions with -0.54 kg N 2 O-N ha -1 for a sorghum-sudan-grass-mixture. The result of our calculation based on a systematic literature search also shows only a very small increase in N 2 O emissions from cover cropping.…”
Section: Resultsmentioning
confidence: 99%
“…The overall conclusion of the meta-analysis is that cover cropping increases N 2 O emissions only to a very small extent and that the variability is very large. For example, compared to a chemical fallow system, Olofsson and Ernfors [ 39 ] identified the highest value with 1.80 kg N 2 O-N ha -1 for oilseed radish, whereas Preza-Fontes et al [ 40 ] identified the lowest emissions with -0.54 kg N 2 O-N ha -1 for a sorghum-sudan-grass-mixture. The result of our calculation based on a systematic literature search also shows only a very small increase in N 2 O emissions from cover cropping.…”
Section: Resultsmentioning
confidence: 99%